Could continuous cover forestry be an economically and environmentally feasible management option on drained boreal peatlands? - Nieminen, M.; Hökkä, H.; Laiho, R.; Juutinen, A.; Ahtikoski, A.; Pearson, M.; Kojola, S.; Sarkkola, S.; Launiainen, S.; Valkonen, S.; Penttilä, T.; Lohila, A.; et al. (Forest Ecology and Management, 2020)
Environmental and economic performance of forestry on drained peatlands was reviewed to consider whether continuous cover forestry (CCF) could be a feasible alternative to even-aged management (EM). CCF was regarded feasible particularly because continuously maintaining a tree stand with significant transpiration and interception capacity would decrease the need for ditch network maintenance. Managing CCF forests in such a way that the ground water levels are lower than in clear-cut EM forests but higher than in mature EM forests could decrease greenhouse gas emissions and negative water quality impacts caused both by anoxic redox reactions and oxidation and mineralization of deep peat layers. Regeneration studies indicated potential for satisfactory natural regeneration under CCF on drained peatlands. An economic advantage in CCF over EM is that fewer investments are needed to establish the forest stand and sustain its growth. Thus, even if the growth of trees in CCF forests were lower than in EM forests, CCF could at least in some peatland sites turn out to be a more profitable forest management regime. An advantage of CCF from the viewpoint of socially optimal forest management is that it plausibly reduces the negative externalities of management compared to EM. We propose that future research in drained peatland forests should focus on assessing the economic and environmental feasibility of CCF. Peer reviewed